The Factors of Ensuring Sustaining Manufacturing Competitiveness (Eurasian Journal of Engineering and Technology, 2022)
A strong and advanced industry ensures full competitiveness of the national economy, and innovative and technological renewal of enterprises increases the overall stability of the economy of Uzbekistan. Development aimed at stabilization of economic processes requires the extensive introduction of innovative changes in all directions of production activity based on the achievements of scientific and technical progress. In the article increasing the number of new types of complex products with new consumer characteristics to the market and increasing their quality, factors aimed at successfully solving these problems are shown